ИССЛЕДОВАНИЕ СТЕПЕНИ ОЧИСТКИ СТОЧНЫХ ВОД С ПОМОЩЬЮ ФОТОДИНАМИЧЕСКОЙ ЦЕОЛИТОВОЙ УСТАНОВКИ ФДЦ-3 (Experimental biology, 2015)
Diagnostic investigation of the cleaning of sewage was held with the help of the Photodynamic Zeolite plant (PZP-3) purpose-built by the Center of Biophysical Ecology of Al-Pharaby Kazakh National University, under Academician, Professor InyushinV.M. guidance. Testify to the fact, that the using of the sewage cleaning plant may be effective and it will be given an option of removing heavy elements compounds and non-ferrous metals
Keywords: Diagnostic investigation; PZP-3